Perspektif Hukum Humaniter Internasional terhadap Penggunaan Autonomous Weapon System (Drone Kamikaze Shahed-136) dalam Konflik Rusia-Ukraina - Silaen, Angeline Christy; Salwa, Rachel Amanda (Media Hukum Indonesia (MHI), 2025)
This article provides a critical analysis of the deployment of the Shahed-136 autonomous kamikaze drone within the context of International Humanitarian Law (IHL) amid the Russia-Ukraine conflict. It scrutinizes fundamental IHL principles—including distinction, proportionality, and the prohibition of superfluous suffering—in relation to the drone’s operational capabilities and documented impact. By examining verified incidents of civilian casualties and damage to civilian infrastructure, the study raises pressing concerns about compliance with established legal norms. Furthermore, it explores the complex legal and ethical dilemmas posed by autonomous targeting systems and the diminished role of human oversight. The article also delves into issues of accountability and the formidable challenges in enforcing international legal frameworks against autonomous weapon systems. Ultimately, it underscores the urgent necessity for enhanced international regulatory mechanisms and robust oversight to address the humanitarian risks inherent in the evolving landscape of autonomous warfare.